Conceptual aspect of children's literature as a phenomenon of the general literary process - Ступницька, Наталія Миколаївна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2018)
The article deals with approaches to the definition of the concept of "children's literature". It is noted in the article that the place of children's literature in the general literary process, the criteria and peculiarities of its separation, as a separate component of the development of literature, is still the subject of lively discussions among researchers. It is asserted that literature for children is not an isolated phenomenon of the general literary process; it has been influenced not only by folklore, but also by major literary trends and tendencies. It is emphasized in the article that literature in general, and children’s one in particular, is a part of the social and historical context and the social, religious and family traditions of the children's reading circle are changing because of the developing of the social and historical context. It is revealed that the social and cultural context predetermines in every concrete historical period the priority of the functions of children's literature as a specific verbal and artistic art which is closely connected with the processes of upbringing and education.